Frequency of Celiac Disease in Patients with Hypothyroidism. (28th March 2012) - Mehrdad, Mojtaba; Mansour-Ghanaei, Fariborz; Mohammadi, Fereshteh; Joukar, Farahnaz; Dodangeh, Salimeh; Mansour-Ghanaei, Roya
Abstract : Background . Celiac disease (CD) is closely associated with other autoimmune endocrine disorders, particularly autoimmune thyroid disease. The aim of this study was to find the frequency of celiac disease in patients with hypothyroidism in Guilan province, north of Iran. Methods . A total of 454 consecutive patients with hypothyroidism underwent celiac serological tests antiGliadin antibodies (AGA), antitissue transglutaminase antibodies (IgA-tTG) and antiendomysial antibodies (EMA-IgA). Small intestinal biopsy was performed when any of celiac serological tests was positive. Results . Eleven (2.4%) patients were positive for celiac serology, and two patients with documented villous atrophy were diagnosed with classic CD (0.4%; 95%). Two patients with classic CD had Hashimoto's thyroiditis (HT) (0.6%; 95%). Six (54.5%) of 11 were suffering from overt hypothyroidism and 45.5% from subclinical hypothyroidism. Six (54.5%) had HT, and 45.5% had nonautoimmune hypothyroidism. Conclusions . In this study, prevalence of CD was lower than other studies. Most of the patients with CD were suffering from HT, but there was no significant statistical relation between CD and HT.